Analysis of Financial Statements Based on Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM): Analisis Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK EMKM) - Shabrina, Adza Razan Nur; Nurasik, Nurasik (Indonesian Journal of Innovation Studies, 2022)
The type of research used is a qualitative research method, is a case study and is aimed at the existing facts. The data collection technique used is by means of observation, interviews and documentation. Data analysis techniques are made with the following stages: 1) Outlining the financial statements of PT. Al-Misfalah in 2020. 2) Review, compare and analyze the financial statements of PT. Al-Misfalah according to SAK EMKM to assess conformity. 3) Drawing conclusions from the results of the study on the implementation of SAK EMKM in the financial statements of PT. Al-Misfalah. The results of research and discussion explain that the financial statements of PT. The majority of Al-Misfalah have complied with SAK EMKM. However, there are things that do not meet the provisions, namely the recording of tax expense in the income statement is not separated from other expenses and the financial statements do not make notes to the financial statements.